HANDGRIP STRENGTH AND BALANCE PERFORMANCES AMONG COMMUNITY DWELLING OLDER ADULTS WITH AND WITHOUT COGNITIVE IMPAIRMENT - Azreen Omar; Muhaini Mustafa; Azliyana Azizan (Journal of Islamic, Social, Economics and Development, 2021)
This present study aims to determine the differences of handgrip strengths and balance performances among older adults with and without cognitive impairments and to determine its correlation between these variables. One hundred fourteen subjects were recruited via convenience sampling and had completed the Montreal cognitive assessment to assess for their cognitive functions. Data on demographics, handgrip strength (as measured by Jamar dynamometer), and balance (as measured by timed-up and go test) were collected. Analysis showed a significant difference in handgrip strength for males older between groups [t(66.944)=3.665, p=0.00] , females older between groups [t(42)=3.17, p=0.03], also in balance performance for males older for both groups [t(22.177)=4.031, p=0.03]. There was a strong, positive correlation between the two variables for older males without the ci group [r=0.48, p=0.00], with high cognitive functions associated with stronger grip strength. Similarly, balance performances showed a significant negative correlation between males in the ci group [r=-0.537, p=0.018], and females older without ci group show positive correlation [r=0.516, p=0.01], respectively. Changes in global cognitive functions may affect handgrip performance and balance deficits among community-dwelling older adults.